Turn a blind eye [compact disc, unabridged] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- William Warwick novels, 2021)
Going undercover to expose corruption in the Metropolitan Police Force, Detective Inspector William Warwick is compromised by a high-profile trial and a teammate's romantic relationship with his suspect.